Improving the Performance of Micro, Small and Medium Enterprises in Indonesia: The Role of Financial Technology - Abdul Rasyid (Journal of Economics and Business (JECOMBI), 2023)
The Industrial Revolution 4.0 era presents a challenge for a country to transform traditional business models into technological systems. The adoption of innovative technology in the financial sector (Financial Technology) necessitates a quick shift to a more conservative business style. As the usage of internet technologies for business transactions grows, Indonesia is a large market for FinTech. FinTech has the potential to be a solution to the problem of MSMEs' lack of funding. MSMEs play a key role in supporting the country's economic development in an era of increasingly fast economic expansion. However, many MSMEs in Indonesia continue to encounter a variety of challenges, particularly in terms of inadequate financial access. The purpose of this study is to examine the impact of financial technology (FinTech) on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. This study employs a qualitative approach to collect data and examine the impact of financial technology adoption on MSMEs. According to the findings of the study, the application of Financial Technology (Fintech) has a considerable positive impact on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Fintech fosters the development of more modern business models, increases financial inclusion, increases operational efficiency, protects against corporate risks, facilitates market expansion, and aids in better financial management. Fintech, in this function, not only removes financial access hurdles, but also creates new chances for MSMEs to compete on a global scale, promote national economic growth, and make a beneficial effect in the digital business world. As a result, Fintech has enormous potential to become a driving force for MSME growth and to aid the overall development of the Indonesian economy.